Apixaban, rivaroxaban, and dabigatran use in patients undergoing catheter ablation for atrial fibrillation using the second‐generation cryoballoon. Issue 11 (28th August 2017) - Tscholl, Verena; Lsharaf, Abdullah Khaled‐A.; Lin, Tina; Bellmann, Barbara; Nagel, Patrick; Lenz, Klaus; Landmesser, Ulf; Roser, Mattias; Rillig, Andreas
Abstract : Background: Data are limited on the safety of periprocedural anticoagulation with novel oral anticoagulants (NOACs) in patients undergoing pulmonary vein isolation (PVI) using the second‐generation cryoballoon (CB) for the treatment of atrial fibrillation. Hypothesis: We hypothesized that the incidence of acute periprocedural complications in patients undergoing PVI do not differ between patients treated with VKA compared to NOACs. Methods: In 200 consecutive patients (mean age, 64.3 _ 10.6 years; female, n = 83) with symptomatic atrial fibrillation, PVI using the second‐generation 28‐mm CB was performed. In patients treated with NOACs, the medication was stopped the day of the procedure and continued the evening after the procedure with a reduced dosage. Patients treated with phenprocoumon were continued on uninterrupted phenprocoumon with a target INR of 2 to 3. If INR was <2, bridging with low‐molecular‐weight heparin was performed. Results: Forty‐seven of 200 patients (23.5%) were treated with a vitamin K antagonist (VKA) and 55 (27.5%) were treated with apixaban, 67 (33.5%) with rivaroxaban, and 31 (15.5%) with dabigatran. Seven (3.5%) major complications occurred in the overall population. Major bleeding complications did not differ significantly between the 2 groups (P = 0.23). One patient taking VKA had a pericardial tamponade at the end of the procedure; 2 patients treated with apixaban developed a groin hematoma requiring surgical intervention. Transient ischemic attack occurred in 1 patient of the apixaban and rivaroxaban group. Conclusions: Apixaban, rivaroxaban, and dabigatran, compared with uninterrupted VKA, did not show a higher risk for major bleeding or ischemic complications in patients undergoing PVI using the second‐generation CB.